Traditional Cardiovascular Risk Factors Associated with Diagonal Earlobe Crease (Frank Sign) in Mexican Adults: Aging, Obesity, Arterial Hypertension, and Being Male Are the Most Important - Rogelio Molina-Gallardo; Nomely S. Aurelien-Cabezas; Daniel Tiburcio-Jimenez; Jorge E. Plata-Florenzano; Jose Guzman-Esquivel; Iram P. Rodriguez-Sanchez; Margarita L. Martinez-Fierro; Roque Molina-Osorio; Adrian A. De-la-Madrid-Cernas; Jorge Armando Barriguete-Melendez; Ivan Delgado-Enciso (International Journal of Hypertension)
Introduction. Cardiovascular risk factors such as obesity, type 2 diabetes, hypertension, smoking, and dyslipidemia enfold heart disease morbimortality. Diagonal earlobe crease has been proposed as a prognostic marker of extension and severity of illness in patients with acute coronary syndrome. But its usefulness remains unclear in patients with or without coronary disease. Methods. A case-control study was carried out on a total of 805 patients with and without cardiovascular risk factors or acute coronary syndrome. Univariate and multivariate binary logistic regression analyses were used to determine the probability of having diagonal earlobe crease with the presence of cardiovascular risk factors and acute coronary syndrome. Data were summarized as odds ratio with 95% confidence intervals and P values. Results. An unadjusted (univariate) analysis showed that being male, being older than 55 years, obesity, type 2 diabetes mellitus, arterial hypertension, smoking, and dyslipidemia, as well as having acute coronary syndrome, were associated with the presence of diagonal earlobe crease. The multivariate analysis showed that men (OR 1.6, 95% IC 1.1–2.4, P=0.007), being over 55 years old (OR 4.8, 95% IC 3.2–7.2, P<0.001), being obese (OR 2.1, 95% IC 1.4–3.1, P<0.001), having arterial hypertension (1.5, 95% IC 1.1–2.3, P=0.025), or suffering from acute coronary syndrome (OR 5.3, 95% IC 2.5–11.1, P<0.001), were independent factors associated with diagonal earlobe crease. The rest of cardiovascular risk factors were not relevant in the multivariate model. Conclusions. In Mexican adults, having an acute coronary syndrome is not the only factor associated with diagonal earlobe crease but also being a man, older than 55 years, having high blood pressure and obesity. Diagonal earlobe crease may simply be caused by changes in the skin and connective tissues of the ears because of the aging process, obesity, and/or being male. These factors, by themselves, enfold cardiovascular risk due to well-known pathophysiological causes.